A View from Above of the Global Poliomyelitis Situation: Pakistan Strategies for Polio Eradication (Journal of Asian Development Studies, 2024)
Throughout history, humanity has encountered several catastrophes, such as natural disasters and the emergence of countless contagious diseases. Poliomyelitis is one such disease. The initial instances of the sickness emerged in the 1940s, prompting health authorities and specialists to develop a vaccine to enhance children's resistance to the virus. Subsequently, polio workers worldwide are diligently endeavouring to raise awareness regarding the crucial significance of polio vaccination, particularly in the tribal regions of Pakistan. This is because the inhabitants of these areas are predominantly underprivileged and uneducated, resulting in their reluctance to vaccinate their children due to apprehensions about safety, as well as religious and misconceptions about the vaccine. The objective of these efforts is to ensure that every kid in Pakistan and Afghanistan receives appropriate immunization in order to halt the spread of the virus by the year 2025.